Financial Hardship, Hope, and Life Satisfaction Among Un/Underemployed Individuals With Psychiatric Diagnoses: A Mediation Analysis - Jiménez-Solomon, Oscar; Primrose, Ryan; Moon, Ingyu; Wall, Melanie; Galfalvy, Hanga; Méndez-Bustos, Pablo; Cruz, Amanda G.; Swarbrick, Margaret; Laing, Taína; Vite, Laurie; Kelley, Maura; Jennings, Elizabeth; et al. (Frontiers in Psychiatry, 2022)
Background: Individuals with psychiatric diagnoses who are unemployed or underemployed are likely to disproportionately experience financial hardship and, in turn, lower life satisfaction. Understanding the mechanisms though which financial hardship affects life satisfaction is essential to inform effective economic empowerment interventions for this population. Aim: To examine if subjective financial hardship (SFH) mediates the relationship between objective financial hardship (OFH) and life satisfaction (LS), and whether hope, and its agency and pathways components, further mediate the effect of SFH on LS among individuals with psychiatric diagnoses seeking employment. Methods: We conducted structured interviews with participants (N=215) of two peer-run employment programs using indicators of OFH and SFH and standardized scales for hope (overall hope, hope agency, and hope pathways) and LS. Three structural equation models were employed to test measurement models for OFH and SFH, and mediational relationships. Covariates included gender, age, psychiatric diagnosis, race/ethnicity, education, income, employment status, SSI/SSDI receipt, and site. Results: Confirmatory factor analysis for items measuring OFH and SFH supported two separate hypothesized factors. OFH had a strong and significant total effect on SFH (standardized beta (B)= .68) and LS (B= .49), and a weak-to-moderate effect on hope (B= -.31). SFH alone mediated up to 94% of the effect of OFH on LS (indirect effect B= -.46, p<.01). The effect of SFH on LS through hope was small (indirect effect B=-.09, p<.05), primarily through hope agency (indirect effect B=-.13, p<.01) and not hope pathways. Black and Hispanic ethno-racial identification seemed to buffer the effect of financial hardship on hope and LS. Individuals identifying as Black reported significantly higher overall hope (B=.41-.47) and higher LS (B=.29-.46), net of the effect of OFH and SFH. Conclusions: SFH is a strong mediator of the relationship between OFH and LS in our study of unemployed and underemployed individuals with psychiatric diagnoses. Hope, and particularly its agency component, further mediate a modest but significant proportion of the association between SFH and LS. Economic empowerment interventions for this population should address objective and subjective financial stressors, foster a sense of agency, and consider the diverse effects of financial hardship across ethno-racial groups.